ANALISIS KOMPARATIF PENDAPATAN USAHATANI DAN MARJIN PEMASARAN PADI SAWAH ORGANIK DENGAN ANORGANIK DI DESA SUMBERSUKO JAYA KECAMATAN BELITANG KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
This research is aimed to : 1) count the comparative pendapatan of organic rice with anorganic rice. 2) count how much the marketing marjin of organic rice and anorganic rice. This research was done in East Ogan Komering Ulu regency which was selected purposively. The method of research used in this research was survey method. The sampling farmers were selected by using disproporsionate random sampling and the sampling farmers were 30 farmers. The result of the research shows that : 1) The marketing run in Lengkiti district consist three marketing channels and the most efficient of marketing channel is channel I,because channel I have short channel comparing with the other channel and marketing cost of channel I is lower than the marketing profit. 2) The marketing marjin values obtained by the agent level of the village is the biggest it is Rp 11.300/kg from organic rice, and the agent of district area at channel III is the biggest comparing with the other marketing institutions, that is Rp 700 per kg to agent of the village at channel I and Rp 650 to agent of the district at channel III..